The cultural heritage of Nagaland - Chophy, G. Kanato; Chaudhuri, S. K. (Routledge, Taylor & Francis Group, 2024)
"This volume gives an in-depth account of cultural heritage of Nagaland covering important themes like cultural beliefs, traditional knowledge, material culture, and social institutions. Contributors from diverse dis ciplines and backgrounds have delved into the cultural heritage of the state's variegated tribes. Nagaland a hilly state in North-East India had been the centre of British colonialism and American Baptist mission. This cultural contact is significantly reflected in the socio-cultural life, and the contributors have shed light on the continuities and changes. This volume highlights the multiplicity of cultural traditions that are specific to various tribes inhabiting sixteen districts of Nagaland, since their experiences of modernity and cultural contact with 'others' have been diverse.The contributors have mainly focussed on the cultural heritage of the majority Naga tribes, but other tribes like the Kukis and Kacharis are part and parcel of the cultural melting pot of Nagaland, and this volume in a way underscores the cultural exchange and interactions."